Impact of Preoperative Specialty Consults on Hospitalist Comanagement of Hip Fracture Patients. Issue 1 (21st August 2019) - Bellas, Nicholas; Stohler, Sherry; Staff, Ilene; Majk, Karolina; Lewis, Courtland; Davis, Stephen; Kumar, Mandeep
Abstract : BACKGROUND: Hip fractures typically occur in frail elderly patients. Preoperative specialty consults, in addition to hospitalist comanagement, are often requested for preoperative risk assessment. OBJECTIVE: Determine if preoperative specialty consults meaningfully influence management and outcomes in hip fracture patients, while being comanaged by hospitalists DESIGN: Retrospective cohort study SETTING: Tertiary care hospital in Connecticut PATIENTS: 491 patients aged 50 years and older who underwent surgery for an isolated fragility hip fracture, defined as one occurring from a fall of a height of standing or less. INTERVENTION: Presence or absence of a preoperative specialty consult MEASUREMENTS: Time to surgery (TTS), length of hospital stay (LOS), and postoperative complications RESULTS: 177 patients had a preoperative specialty consult. Patients with consults were older and had more comorbidities. Most consult recommendations were minor (72.8%); there was a major recommendation only for eight patients (4.5%). Multivariate analysis demonstrates that consults are more likely to be associated with a TTS beyond 24 hours (Odds Ratio [OR] 4.28 [2.79‐6.56]) and 48 hours (OR 2.59 [1.52‐4.43]), an extended LOS (OR 2.67 [1.78‐4.03]), and a higher 30‐day readmission rate (OR 2.11 [1.09‐4.08]). A similar 30‐day mortality rate was noted in both consult and no‐consult groups. CONCLUSIONS: The majority of preoperative specialty consults did not meaningfully influence management and may have potentially increased morbidity by delaying surgery. Our data suggest that unless a hip fracture patient is unstable and likely to require active management by a consultant, such consults offer limited benefit when weighed against the negative impact of surgical delay.